Analysis of the Implementation of Clinical Pharmacy Services Based on Minister of Health Regulation No. 73 of 2016 at the Kapanewon Minggir Pharmacy, Sleman, Yogyakarta - Veronika Livia Gavrilayanti; Titien Siwi Hartayu (Jurnal Locus Penelitian dan Pengabdian, 2026)
Clinical pharmacy services are a mandatory component of pharmaceutical service standards in community pharmacies, as stipulated in the Regulation of the Minister of Health of the Republic of Indonesia Number 73 of 2016. This study aimed to analyze the implementation of clinical pharmacy services based on PMK RI Number 73/2016 and to identify supporting and inhibiting factors affecting their implementation in pharmacies. The study employed a descriptive analytic design with a mixed-method approach. The study subjects consisted of four pharmacists in charge of pharmacies, selected based on inclusion and exclusion criteria. Data were collected through document observation and observation of clinical pharmacy service implementation using a checklist based on PMK 73/2016, as well as in-depth interviews to further explore the findings. Data were analyzed descriptively and validated using triangulation methods. Document observation results revealed differences in the completeness of standard operating procedures for clinical pharmacy services among pharmacies, with Pharmacy B categorized as good (?80%), Pharmacy A as moderate (?61%), while Pharmacies C and D were categorized as poor (?60%). Observation of service implementation showed that prescription review and dispensing activities had been well implemented in all pharmacies. In contrast, drug information services remained limited, and counseling services varied among pharmacies. Other clinical pharmacy services, including home pharmacy care, drug therapy monitoring, and adverse drug reaction monitoring, had not been implemented in all pharmacies. Based on interview findings, the gap between document completeness and service implementation was influenced by limited knowledge, the absence of supporting systems and documentation, limited human resources, and low managerial support. Therefore, strengthening support systems, enhancing pharmacists’ capacity, and implementing more focused supervision and guidance on clinical pharmacy services are required.